2007
DOI: 10.1111/j.1537-2995.2007.01482.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the risk of transfusion‐transmissible viral infection through blood donor selection: the Australian experience 2000 through 2006

Abstract: BACKGROUND: Selection of voluntary donors who are at low risk of transfusion‐transmissible viral infection (TTVI) is central in maintaining the safety of the blood supply. Evaluation of its effectiveness and the dynamics of the process may offer opportunities to further improve transfusion safety. STUDY DESIGN AND METHODS: The impact of donor selection on prevalence of TTVI was analyzed in all allogeneic donations in Australia between July 2000 and June 2006 by interviewing donors found to have a TTVI. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 47 publications
(90 reference statements)
10
67
2
Order By: Relevance
“…A much higher HBsAg prevalence (8.1%) was detected in 480 healthcare workers investigated by Kondili et al [62] in 2004 in Albania, in accordance with the widespread of HBV infection in this country. In this study, the highest rates of HBsAg positivity were found in the youngest age group (11.4% in the aged [20][21][22][23][24][25][26][27][28][29][30] and in the auxiliaries (12.6%), but a high HBsAg prevalence (7.2%-7.5%) was also found in the healthcare workers aged over 30. The anti-HBc seroprevalence was also extremely high (70%) in this study and was associated with an age over 40 (OR = 2.9; 95%CI: 1.9-4.6).…”
Section: Studies On Hbv Infection In Healthcare Workersmentioning
confidence: 97%
See 1 more Smart Citation
“…A much higher HBsAg prevalence (8.1%) was detected in 480 healthcare workers investigated by Kondili et al [62] in 2004 in Albania, in accordance with the widespread of HBV infection in this country. In this study, the highest rates of HBsAg positivity were found in the youngest age group (11.4% in the aged [20][21][22][23][24][25][26][27][28][29][30] and in the auxiliaries (12.6%), but a high HBsAg prevalence (7.2%-7.5%) was also found in the healthcare workers aged over 30. The anti-HBc seroprevalence was also extremely high (70%) in this study and was associated with an age over 40 (OR = 2.9; 95%CI: 1.9-4.6).…”
Section: Studies On Hbv Infection In Healthcare Workersmentioning
confidence: 97%
“…Worthy of note, the screening of blood donors for markers of HBV infection has dramatically reduced the risk of HBV transmission through the transfusions of blood and blood products. At present, this risk is estimated as 1-4 cases per million blood components transfused in low-prevalence areas [29] and around 1 case per 20000 blood transfusions in high-prevalence regions [30] . The transfusion of infected blood and blood products was the most prominent route of transmission of HCV infection until 1989 [1,31] .…”
Section: Risk Factors For the Acquisition Of Hbv And Hcv Infectionmentioning
confidence: 99%
“…Additionally, new pathogens transmitted by risky behavior that are not yet tested in blood donors may appear 26 . The selection of donors is still the only way to prevent the transmission of infected blood donated during the immunological testing window 8,27,28 . One of the steps in this selection is the confi dential self-exclusion (CSE) form on which the blood donors can exclude their donated blood without providing any justifi cation 28,29 .…”
Section: Methods Resultsmentioning
confidence: 99%
“…Current deferral rates for at-risk behaviour suggest most donors acknowledge their risk; however, it is well documented that a few donors with transmissible infections do fail for one reason or another to declare their risk [42,43,44,45]. Inaccurate information may be communicated intentionally or unintentionally either because they misunderstood the questions asked or because they were unaware or have forgotten certain risk behaviour [29].…”
Section: Discussionmentioning
confidence: 99%